Education of Stunting Prevention Convergence with Development Planning for Rumah Desa Sehat Facilitation as a Community Center (Non-Physical) in Rangga Surya Village - Annisa Annisa (UMBanjarmasin, 2022)
Convergence is an approach to provide coordinated and integrated interventions in order to jointly prevent stunting. The implementation of convergent interventions is carried out by aligning the planning, budgeting, implementation, monitoring, and control of cross-sector activities, especially priority groups in the village. One of the efforts to convergence stunting prevention in the village is through community participation approach with the development of Rumah Desa Sehat as community centers. Rangga Surya Village in Belawang District is one of the locations where there is a priority group for accelerating stunting prevention in Barito Kuala Regency. Therefore, the purpose of this community service is to provide an understanding and direction on the importance of the existence of Rumah Desa Sehat as a gathering place or joint secretariat in the field of health that serves as a joint learning space, aspiration excavation, cultural actualization, community activities, access to information and community health care forums, as well as education and social. The method carried out in community service is by educating and socializing directly to village officials, community leaders and the community in Rangga Surya Village. Education and socialization resulted in an agreement that Rumah Desa Sehat will be established as an effort to accelerate stunting prevention in Rangga Surya Village, Belawang District.